2008
DOI: 10.1080/00365590701547076
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral microwave thermotherapy of the prostate – Evaluation with MRI and analysis of parameters relevant to outcome

Abstract: Coretherm microwave treatment leads to significant intraprostatic necrosis, which is detectable with MRI even 6 months after the treatment. Diffusion-weighted MRI is capable of identifying structural features of the prostate that can predict the length of treatment and the amount of energy needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The treatment catheter used in ProstaLund Feedback Treatment (PLFT, CoreTherm) contains a temperature sensor inserted into the prostate (intraprostatic sensor (IP sensor)) and is used to calculate cell kill [1], which is dependent on tissue temperature and treatment time [1][2][3][4]. The calculated cell kill corresponds to tissue destruction seen on transrectal ultrasound, magnetic resonance imaging and histopathology [5][6][7]. Intraprostatic blood flow can increase considerably as a response to heat [2,8] and thereby act as a coolant by lowering the temperature within the prostate [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment catheter used in ProstaLund Feedback Treatment (PLFT, CoreTherm) contains a temperature sensor inserted into the prostate (intraprostatic sensor (IP sensor)) and is used to calculate cell kill [1], which is dependent on tissue temperature and treatment time [1][2][3][4]. The calculated cell kill corresponds to tissue destruction seen on transrectal ultrasound, magnetic resonance imaging and histopathology [5][6][7]. Intraprostatic blood flow can increase considerably as a response to heat [2,8] and thereby act as a coolant by lowering the temperature within the prostate [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported the effectiveness of hyperthermia using various materials and methods of heating, such as inductive heating using electromagnetic materials,6, 7 dielectric heating including radiofrequency ablation (RFA),8–10 and microwave coagulation therapy (MCT) 11, 12. However, conventional thermotherapy has been reported to have a few problems.…”
mentioning
confidence: 99%
“…4,5 Many researchers have reported the effectiveness of hyperthermia using various materials and methods of heating, such as inductive heating using electromagnetic materials, 6,7 dielectric heating including radiofrequency ablation (RFA), [8][9][10] and microwave coagulation therapy (MCT). 11,12 However, conventional thermotherapy has been reported to have a few problems. For example, it has been reported that a temperature above 42.5 C caused tumor cell death in vitro, 13 but, for mammalian cells, a temperature above 43 C resulted in irreversible damage to both malignant cells and surrounding normal intact cells 14 and tissues.…”
mentioning
confidence: 99%